Recession farming practices and their linkage to hydroclimatic risks in Kilombero Valley - Neshafati Fwaya; Yonika M. Ngaga; Mariele Evers; Makarius C. S. Lalika; Kristian Näschen (Discover Agriculture)
Abstract Kilombero Valley is one of the African floodplain ecosystems currently under pressure due to significant water-related investments and hydroclimatic risks; threatening its function. This current study characterized flood recession farming practices and their significance in reducing hydroclimatic risks. Specifically, the study focused on dominant crops in recession farming, crop yield, income earned in recession farming, seasonal water variation, and farmers’ perception of hydroclimatic risks. The study is a mix of quantitative and qualitative research, in which primary data were collected through interviews and focus group discussions. Hydrological data were obtained from the Rufiji Basin Water Board. The quantitative data were analyzed statistically using means, standard deviations, coefficients of variation, frequencies, percentages, and the seasonal Mann–Kendall (MK) statistical test. Content analysis was employed to identify the major themes from the focus group discussions. The study found that maize crop producers dominate recession farming, followed by rice producers. These crops are essential for household food and nutritional security and serve as a source of income during the dry season in the study villages. Yields and incomes from recession farming vary across the different villages. Additionally, our seasonality analysis revealed that peak river discharges align well with peak rainfall periods. The farmers were aware of hydro-climatic risks and were able to develop coping strategies. Low yield in recession farming highlights the presence of constraints that could be addressed through improved policy and effective management approaches.